2021
DOI: 10.3390/medicina57121384
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Inflammatory Markers in Patients with Suspected Acute Appendicitis

Abstract: Background: Laboratory tests of inflammatory mediators are routinely used in the diagnosis of acute appendicitis (AA). The aim of this study was to evaluate the differences of dynamics of inflammatory markers of the blood in patients with suspected acute appendicitis between complicated AA (CAA), non-complicated AA (NAA), and when AA was excluded (No-AA). Methods: This was a retrospective analysis of prospectively collected data of patients presented to the Emergency Department (ER) of a tertiary hospital cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…In appendicitis, prostaglandin E2 (PGE2) is increased in serum and peritoneal fluid, and its levels correlate with the severity of inflammation [56]. A study found that PGE2 had a sensitivity of 83% and specificity of 93% for diagnosing acute appendicitis [57].…”
Section: Inflammatory Cascade and Cytokines Chemokines And Prostaglan...mentioning
confidence: 99%
“…In appendicitis, prostaglandin E2 (PGE2) is increased in serum and peritoneal fluid, and its levels correlate with the severity of inflammation [56]. A study found that PGE2 had a sensitivity of 83% and specificity of 93% for diagnosing acute appendicitis [57].…”
Section: Inflammatory Cascade and Cytokines Chemokines And Prostaglan...mentioning
confidence: 99%
“…7 Pada penelitian Kaminskas didapatkan prevalensi dan insiden apendisitis akut meningkat dan berbanding lurus dengan usia. 8 Pada penelitian ini didapatkan prevalensi pasien apendisitis akut sebanyak 20 (62,5%) orang berjenis kelamin laki-laki dan 12 (37,5%) orang berjenis kelamin perempuan. Penelitian serupa yang dilakukan oleh Jahangiri didapatkan prevalensi apendisitis akut terjadi lebih sering pada pria dibanding wanita sebanyak 54%.…”
Section: Diskusiunclassified
“…Acute appendicitis (AA) is the most common general surgical emergency worldwide, but its diagnosis remains challenging [ 1 ]. Traditional diagnostic tools—laboratory and clinical parameters and transabdominal ultrasound (TUS)—lack sensitivity and specificity for accurate diagnosis [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. On the one hand, undiagnosed AA can cause lethal consequences.…”
Section: Introductionmentioning
confidence: 99%